Penguatan Moderasi Beragama melalui Pendidikan Agama Islam - Sudarmin Sudarmin; Amaluddin Amaluddin (FKIP UNSULTRA, 2025)
Religious moderation is an important principle in maintaining the harmony of religious life in multicultural Indonesia. Islamic Religious Education (PAI) has a strategic role in forming a generation that not only understands Islamic values ​​textually, but is also able to implement these values ​​contextually and inclusively. This study aims to explore various current literature that discusses the role of PAI in strengthening religious moderation at various levels of education. The research method used is a literature study by reviewing scientific journals, books, and relevant education policy documents from the last five years. The results of the study show that strengthening religious moderation through PAI includes five main aspects: integration of moderation values ​​in the curriculum, the role of teachers as agents of moderation, contextual learning methods, the use of educational digital media, and a school environment that supports tolerance values. This study recommends strengthening the capacity of PAI teachers and improving the curriculum as the main strategy. With a holistic approach, PAI can be the main pillar in forming moderate, tolerant, and inclusive characters in students. This research is expected to contribute to the development of religious education policies that are relevant to the challenges of the times.